Risk of persistent cranial nerve injury after carotid endarterectomy. - Cunningham, E; Bond, R; Mayberg, MR; Warlow, C; Rothwell, P (2004)
OBJECT: Cranial nerve injuries, particularly motor nerve injuries, following carotid endarterectomy (CEA) can be disabling and therefore patients should be given reliable information about the risks of sustaining such injuries. The reported frequency of cranial nerve injury in the published literature ranges from 3 to 23%, and there have been few series in which patients were routinely examined before and after surgery by a neurologist. METHODS: The authors investigated the risk of cranial nerve injuries in patients who underwent CEA in the European Carotid Surgery Trial (ECST), the largest series of patients undergoing CEA in which neurological assessment was performed before and after surgery. Cranial nerve injury was assessed and recorded in every patient and persisting deficits were identified on follow-up examination at 4 months and 1 year after randomization. Risk factors for cranial nerve injury were examined by performing univariate and multivariate analyses. There were 88 motor cranial nerve injuries among the 1739 patients undergoing CEA (5.1% of patients; 95% confidence interval [CI] 4.1-6.2). In 23 patients, the deficit had resolved by hospital discharge, leaving 3.7% of patients (95% CI 2.9-4.7) with a residual cranial nerve injury: 27 hypoglossal, 17 marginal mandibular, 17 recurrent laryngeal, one accessory nerve, and three Homer syndrome. In only nine patients (0.5%; 95% CI 0.24-0.98) the deficit was still present at the 4-month follow-up examination; however, none of the persisting deficits resolved during the subsequent follow up. Only duration of operation longer than 2 hours was independently associated with an increased risk of cranial nerve injury (hazard ratio 1.56, p < 0.0001). CONCLUSIONS: The risk of motor cranial nerve injury persisting beyond hospital discharge after CEA is approximately 4%. The vast majority of neurological deficits resolve over the next few months, however, and permanent deficits are rare. Nevertheless, the risk of cranial nerve injury should be communicated to patients before they undergo surgery.